2015
DOI: 10.1111/jsm.13029
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Concentrations and Cardiovascular Autonomic Neuropathy in Men with Type 1 Diabetes in the Epidemiology of Diabetes Interventions and Complications Study (EDIC)

Abstract: Introduction Previous studies have reported that lower testosterone concentrations are associated with cardiovascular autonomic neuropathy (CAN), a risk factor for cardiovascular events. However, no studies have examined this relationship in men with type 1 diabetes, who are at high risk for CAN. Aim To examine the associations between testosterone concentrations and measures of CAN in a large, well-characterized cohort of men with type 1 diabetes. Methods We conducted an analysis of men in the Diabetes Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In previous work, we and others have reported that adult women with T1D have higher arterial stiffness compared to men [ 49 ]. While sex hormone influences on autonomic function [ 50 ] and microvascular complications [ 51 ] have been reported elsewhere, this is to our knowledge, the first report documenting a potential role for gender as a modifier of arterial stiffness in adolescents with T1D. In the current analysis, although positive associations between PWV and BMI and PWV and blood pressure were perhaps expected [ 2 ], the association between male gender and higher PWV was surprising, and suggests that relationship gender and arterial stiffness changes in relation to pubertal status, a possibility that has been reported elsewhere and that requires further study [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we and others have reported that adult women with T1D have higher arterial stiffness compared to men [ 49 ]. While sex hormone influences on autonomic function [ 50 ] and microvascular complications [ 51 ] have been reported elsewhere, this is to our knowledge, the first report documenting a potential role for gender as a modifier of arterial stiffness in adolescents with T1D. In the current analysis, although positive associations between PWV and BMI and PWV and blood pressure were perhaps expected [ 2 ], the association between male gender and higher PWV was surprising, and suggests that relationship gender and arterial stiffness changes in relation to pubertal status, a possibility that has been reported elsewhere and that requires further study [ 52 ].…”
Section: Discussionmentioning
confidence: 99%